Konsum im Jenseits? - Ekkehart Schlicht (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2006)
– Many contributions to the economics of religion postulate an "afterlife consumption motive." People are assumed to maximize total utility–including afterlife utility. This essay argues that the approach is unsatifactory for several reasons. First, many regularities in religious participation may be explained by ordinary consumption theory without invoking an afterlife; second, there exist religions that do not postulate an afterlife, and there are religions that suppose an afterlife yet do not allow men to influence their fate in the hereafter by good deeds; and third, if afterlife consumption were the foundation for religious demand, we would observe an inflation of promises about afterlife bliss, brought about by competition among the religions. It is proposed to follow David Hume (1775) and see religious demand as originating from the desire of human beings to understand the world and justify their action. This religious motive ("quest for sense") can explain the emergence of ideas about an afterlife and afterlife consumption in monotheistic religions and permits to understand why an inflation of afterlife promises does not occur.
urn:nbn:de:bvb:19-epub-1186-8
Keywords: Z12; 330; religion; afterlife